The prevalence of and risk factors for restless legs syndrome: A nationwide study - AlShareef, Saad Mohammed (Frontiers in Psychiatry, 2023)
Objectives Restless legs syndrome (RLS) is a neglected diagnosis, and most individuals with RLS do not access effective therapies. There has yet to be a nationwide study of the prevalence of and associated risk factors for RLS in Saudi Arabia. Materials and methods A population-wide survey was administered to Saudi Arabian adults to assess RLS prevalence and its association with other clinical and demographic variables. RLS was defined according to 2012 IRLSSG Diagnostic Criteria. Persistent RLS was defined as symptoms occurring more than a few nights each week, and RLS causing significant daytime impairment was defined as symptoms causing “severe” excessive daytime sleepiness measured by the Epworth Sleepiness Scale. Associations were evaluated using univariate analyses and binary logistic regression. Results 10,106 individuals completed the survey. Persistent RLS was reported in 11.9% of participants, which caused significant daytime impairment in 1.2% of participants. In multivariable analysis, younger age (OR 0.96, 95% CI 0.95–0.97; p < 0.001), tobacco smoking (OR 1.28, 95% CI 1.07–1.53; p = 0.008), anxiety (OR 1.34–1.42; p < 0.05), and moderate to severe depressive symptoms (OR 1.52–2.40; p < 0.01) were associated with persistent RLS. Younger age (OR 0.96, 95% CI 0.93–0.99; p = 0.015), female gender (OR 2.28, 95% CI 1.32–3.94; p = 0.003), and moderately severe to severe depressive symptoms (OR 13.59 and 26.7, respectively; p < 0.001) were independently associated with RLS causing significant daytime impairment. Conclusion RLS is common in adults in Saudi Arabia and is often co-morbid with moderate to severe depressive symptoms. Both RLS and depression represent a silent epidemic in Saudi Arabia requiring active inquiry by all healthcare workers to reduce their burden and impact.